2018
DOI: 10.1017/cha.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

‘It's Been an Absolute Nightmare’ – Family Violence in Kinship Care in Victoria

Abstract: Kinship care has become the fastest growing form of out-of-home care in Victoria and is the preferred placement option for children who are unable to live with their parents. Little is known about family violence in kinship care that is perpetrated by a close family member of the child in care (usually the child's mother/father) against the carer(s) and children once the placement has started. In this context, family violence means any act of physical violence, emotional/psychological violence, verbal abuse an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…While maintaining relationships through contact may have benefits for children, such as promoting feelings of belonging and building the child’s identity (León, Jiménez‐Morago and Muñoz‐Silva, 2016), challenges may arise from the relationship between the children’s parent(s) and grandparent caregivers, and conflict around the practicalities of contact (Kiraly and Humphreys, 2013; 2015). In some cases, such conflict has resulted in violence towards the caregiver from the parent(s) (Breman, 2014; Breman, MacRae and Vicary, 2018). Additionally, difficulties that may have led to an SGO being in place – for instance, parental substance misuse or parental mental health difficulties – may continue to play a significant role in family relationships (Holt and Birchall, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While maintaining relationships through contact may have benefits for children, such as promoting feelings of belonging and building the child’s identity (León, Jiménez‐Morago and Muñoz‐Silva, 2016), challenges may arise from the relationship between the children’s parent(s) and grandparent caregivers, and conflict around the practicalities of contact (Kiraly and Humphreys, 2013; 2015). In some cases, such conflict has resulted in violence towards the caregiver from the parent(s) (Breman, 2014; Breman, MacRae and Vicary, 2018). Additionally, difficulties that may have led to an SGO being in place – for instance, parental substance misuse or parental mental health difficulties – may continue to play a significant role in family relationships (Holt and Birchall, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies included in this review did not satisfy the basic criteria of rigor. Breman et al (2018) provided scant details of their methods but were included in the analysis due to the usefulness of the findings. Denby (2015), who also scored 1 for usefulness, only provided a figure for child maltreatment recurrence but with no information about the source of the figure, therefore it was excluded from further analysis.…”
Section: English Language Papersmentioning
confidence: 99%
“…Continued contact with a birth parent may not always be in the child's interest, and can create conflict and potentially expose the child to ongoing abuse (Wellard et al, 2017, Breman et al, 2018. Kinship carers can underplay behavioural difficulties and this could have negative outcomes for assessing special needs or disability (Breman, 2014, Mitchell, 2014.…”
Section: Outcomes For Children In Kinship Carementioning
confidence: 99%
“…Children may be less likely to be reunified with their birth family (Farmer, 2009; Taussig and Clyman, 2011) and US research found that more time in kinship care can be associated with substance abuse, delinquency and poor academic performance (Ryan et al , 2010; Taussig and Clyman, 2011; Font, 2015). Continued contact with a birth parent may not always be in the child's interest, and can create conflict and potentially expose the child to ongoing abuse (Wellard et al , 2017; Breman et al , 2018). Kinship carers can underplay behavioural difficulties and this could have negative outcomes for assessing special needs or disability (Breman, 2014; Mitchell, 2014).…”
Section: Introductionmentioning
confidence: 99%